THE EFFECTIVENESS OF WORK MOTIVATION AND EMPLOYEE ABILITIES IN REGIONAL GOVERNMENT ORGANIZATIONS IN REGENCY IN THE PROVINCE OF GORONTALO - Syamsu Qamar Badu; Novianty Djafri (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
A government organization has predetermined goals. Success in achieving these goals does not only depend on government operational funds, facilities, infrastructure, and technology, but also on human resources. Therefore, this research aims to examine the influence of work motivation and employee abilities on the effectiveness of local government organizations, with the hypothesis that